Case report: in focus IgA nephropathy as a gluten-related disorder - M. E. Mantsaeva; A. G. Borisov; A. A. Stremouhov (Лечащий Врач)
The kidneys can be involved in the pathological process in celiac disease, both in connection with severe metabolic disorders, and as an associated disease. In total, there is evidence of various types of kidney damage in patients with celiac disease, including IgA nephropathy, diabetic nephropathy, membranous nephropathy, membranoproliferative glomerulonephritis, nephrotic syndrome associated with malabsorption, oxalate nephropathy, and the association of celiac disease with chronic renal disease and terminal renal insufficiency in the literature. We describe a case of a 46-year-old man with gluten-related disorders. Given the absence of typical clinical manifestations from the gastrointestinal tract, increased antibodies IgA to tissue transglutaminase and deamidated gliadin peptides, the morphological picture of the duodenal mucosa, do not give grounds for diagnosing celiac disease, but indicate the presence of a gluten-related disorders in the patient. The patient was prescribed a gluten-free diet for a period of 6 months. As a result, an improvement in clinical and laboratory parameters was observed: more stable blood pressure values on standard antihypertensive therapy, a decrease in proteinuria, hematuria, and antibody IgA to tissue transglutaminase and deamidated gliadin peptides. The introduction of a gluten-free diet in the diet of patients with IgA-nephropathy can improve clinical and laboratory parameters, such as blood pressure, proteinuria, hematuria, and probably delay the progression of chronic renaldisease.